Calcium/calmodulin-dependent serine protein kinase CASK modulates the L-type calcium current. (January 2017) - Nafzger, Sabine; Rougier, Jean-Sebastien
Graphical abstract: Highlights: CASK down-regulates the voltage-gated calcium channel Cav1.2. CASK decreases the open probability of Cav1.2 channel. CASK decreases the frequency of opening of Cav1.2 channel. The distal C-terminal part of Cav1.2 counteracts the CASK effect. Abstract: Aim: The L-type voltage-gated calcium channel Cav 1.2 mediates the calcium influx into cells upon membrane depolarization. The list of cardiopathies associated to Cav 1.2 dysfunctions highlights the importance of this channel in cardiac physiology. Calcium/calmodulin-dependent serine protein kinase (CASK), expressed in cardiac cells, has been identified as a regulator of Cav 2.2 channels in neurons, but no experiments have been performed to investigate its role in Cav 1.2 regulation. Methods and results: Full length or the distal C-terminal truncated of the pore-forming Cav 1.2 channel (Cav 1.2α1c), both present in cardiac cells, were expressed in TsA-201 cells. In addition, a shRNA silencer, or scramble as negative control, of CASK was co-transfected in order to silence CASK endogenously expressed. Three days post-transfection, the barium current was increased only for the truncated form without alteration of the steady state activation and inactivation biophysical properties. The calcium current, however, was increased after CASK silencing with both types of Cav 1.2α1c subunits suggesting that, in absence of calcium, the distal C-terminal counteracts the CASK effect. Biochemistry experiments did not reveals neither an alteration of Cav 1.2 channel protein expression after CASK silencing nor an interaction between Cav 1.2α1c subunits and CASK. Nevertheless, after CASK silencing, single calcium channel recordings have shown an increase of the voltage-gated calcium channel Cav 1.2 open probability explaining the increase of the whole-cell current. Conclusion: This study suggests CASK as a novel regulator of Cav 1.2 via a modulation of the voltage-gated calcium channel Cav 1.2 open probability.